Prediction and ecotoxicological effects of runoff induced pesticide contamination in agricultural surface waters : a risk assessment using GIS and microcosms - Dabrowski, James Michael (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001.